2004
DOI: 10.1111/j.0965-075x.2004.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Selection Encounters on Applicants: An Experimental Study into Feedback Effects after a Negative Selection Decision

Abstract: This study investigates the role of feedback in minimizing the psychological impact of a negative selection decision on job applicants. The method and findings of a laboratory experiment into subjects' reactions to rejection, combined with feedback on this decision as well as perceptions of procedural and distributive fairness, are discussed. Subjects participating in the experiment (N 5 119) were asked to complete two GMA tests and were told they had to belong to the 20% best performers to be invited for a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 39 publications
3
38
0
3
Order By: Relevance
“…When learners receive the same feedback without these personalized remarks, making external attributions for this feedback is more likely. A study by Schinkel, van Dierendonck and Anderson (2004) supports this explanation. Providing participants with detailed performance feedback in the context of a negative selection decision sometimes led to more negative participants' reactions, suggesting that the provision of detailed performance feedback is not always as advantageous as often assumed.…”
Section: Discussionmentioning
confidence: 83%
“…When learners receive the same feedback without these personalized remarks, making external attributions for this feedback is more likely. A study by Schinkel, van Dierendonck and Anderson (2004) supports this explanation. Providing participants with detailed performance feedback in the context of a negative selection decision sometimes led to more negative participants' reactions, suggesting that the provision of detailed performance feedback is not always as advantageous as often assumed.…”
Section: Discussionmentioning
confidence: 83%
“…Note that this question is far from trivial, as there are theoretical (Judge, Hulin, & Dalal, 2012) and empirical (Dóci & Hofmans, 2015;Ferris et al, 2011;Schinkel, Van Dierendonck, & Anderson, 2004) indications of substantial and systematic within-person variability in people's CSEs. Judge et al (2012), for example, argued that CSEs can change over a course of minutes, hours, and days in response to working events such as receiving feedback, past performance, and job rewards.…”
Section: The Relationship Between Cses and Job Performancementioning
confidence: 99%
“…In general, results showed that providing personal information enhanced fairness and organizational perceptions but harmed self-perceptions. A similar study by Schinkel, van Dierendonck, and Anderson (2004) examined the effect of providing applicants with bogus performance feedback after rejection decisions. Participants in the feedback condition were told that their performance on the tests fell below the required standard.…”
Section: Introductionmentioning
confidence: 99%